Pyridoxine-dependent epilepsy owing to antiquitin deficiency — mutation in the ALDH7A1 gene. (May 2013) - Jagadeesh, Sujatha; Suresh, Beena; Murugan, V; Suresh, S; Salomans, G S; Struys, E A; Jacobs, C
Abstract : Pyridoxine-dependent epilepsy (PDE) is an inborn error of metabolism resulting from antiquitin deficiency. There is marked elevation of α -amino adipic semi-aldehyde ( α AASA), piperidine-6-carboxylate (P6C) and pipecolic acid. The diagnosis can be confirmed by identifying the mutation in the ALDH7A1 gene in chromosome 5q3l. An 8-year-old Indian girl presented with severe developmental delay and seizures and was found to have pyridoxine-dependent epilepsy owing to an antiquitin mutation. Genetic evaluation of the parents allowed antenatal diagnosis to be made during the next pregnancy.